Super-wideband antenna with modified elliptical-shaped for broad spectrum capability in software-defined radio applications - Fitri Yuli Zulkifli; Aditya Inzani Wahdiyat; Thooriq Maulana; Ali Hanafiah Rambe; Nurhayati Nurhayati (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
The rapid development of wireless communication technology has driven the need for integrating multiple devices into a single platform to improve connectivity. Software-Defined Radio (SDR) stands out as a promising solution but requires antennas with an exceptionally wide bandwidth. This study introduces a super-wideband microstrip antenna designed to meet these needs, covering a frequency range of 0.42 to 40 GHz. The antenna is made using a Taconic TLY-5 substrate, known for its low dielectric loss, and has a simple printed monopole microstrip design with dimensions of 160 × 260 mm². Experimental results demonstrate that the antenna operates efficiently over a broad frequency range of 0.42 to 35.96 GHz, achieving a remarkable bandwidth ratio of 1:85. The antenna exhibits a gain exceeding 2 dBi across the entire frequency range, with a peak gain of 11 dBi, and maintains a total efficiency of over 60 % across this wide frequency spectrum. Its ability to achieve resonance at extremely low frequencies, combined with a remarkable 1:85 bandwidth ratio, significantly contributes to the novelty and impact of this work. This design demonstrates a practical and efficient solution for next-generation communication systems, combining wideband performance with compactness and ease of fabrication.